Strategi 5758 (Maju Mapan) Salatiga dalam Mengatasi Krisis Corporate Image - Valiani Vava Sahara (PAX HUMANA, 2016)
The crisis is an unstable condition and a damaging impact on an organization, as well as the crisis in Super Store 5758 (Maju Mapan) Salatiga due to a case on the alleged sale of reconditioning smartphone that ensnared the owner. This case makes Maju Mapan image tarnished and demanding to pursue a strategy to overcome the crisis of corporate image. To view, the strategy used the descriptive qualitative method. The findings of this study indicate that the crisis management strategy based on a spontaneous idea from the management team of Maju Mapan when the case occurred and the crisis began to appear on the stage of the crisis. Once the case is completed and crisis entered in cleaning phase, the handler of crisis strategy was taken over by the owner to rebuilds relationships with the media, customers, and business partners. This research resulted in a new model of crisis management strategy in managing the crisis of corporate image to the trust was built in the public mind.Keywords: crisis, crisis management, corporate image, crisis strategy of 5758